Population Mobility, Urban Planning and Management in China - Wong, Tai-Chee (Springer, 2015)
This volume contains essays that examine contemporary urban and regional planning and development in China. Through in-depth theoretical and empirical analysis, it provides insights into the urban policies and operational mechanisms of this colossal transitional economy which has presented unprecedented challenges and dynamics.